Trade liberalization & gender wage inequality in Singapore's manufacturing sector. - Lim, Wan Qi. (2013)
Singapore has been one of the most open economies over the past three decades. Based on statistics, the manufacturing sector dominates Singapore’s exports. Due to lack of studies and research on gender wage inequality issue, this paper aims to analyse how trade liberalization affects gender wage inequality in Singapore’s manufacturing sector. This paper uses data from various sources from year 1990 to 2011. Our results show that gender wage inequality issue in Singapore’s manufacturing sector supports the neoclassical theory where trade liberalization narrows the gender wage gap. Females tend to gain in absolute and relative terms. Foreign direct investments and manufacturing export-output are the main factors that have contributed to the improvement in gender wage inequality.